Physical function measures and health-related quality of life in primary care medicine: cross-sectional study - Starkopf, Ann; Müller, Raili; Starkopf, Anu; Aart, Annika; Kull, Mart; Põlluste, Kaja; Lember, Margus; Kallikorm, Riina (Family Medicine & Primary Care Review, 2017)
Background . Health-related quality of life (HRQoL) is an important component of comprehensive management in primary care. Objectives. The purpose of this study was to investigate the relationships between physical performance measures and self-reported HRQoL and to fi nd optimal values of muscle function tests associated with lower HRQoL. Material and methods. From a single primary health care center patient list, 330 subjects were randomly selected. Information about the patient’s age, gender, body mass index and presence of self-reported chronic diseases was collected, as well as analyses for systemic infl ammation and vitamin D. Physical performance was measured by dominant hand grip strength (GS) and a 30-second chair stand test (30-CST). The physical (PCS) and mental (MCS) component scores of the Short-Form-36 Questionnaire (SF-36) were used to evaluate HRQoL. The predictive power of physical function measures were tested with multivariate linear regression analyses. Threshold values for physical function tests were calculated by receiver operating characteristic curves. Results . Multivariate analyses demonstrated that 30-CST was signifi cantly (p < 0.0001) associated with SF-36 summary scores for both genders. Males with 30-CST results under 7 stands and females with results of fewer than 13 stands were in the risk group for having the lowest PCS scores. Results in 30-CST under 12 stands in males and under 13 stands in females were associated with the lowest scores of MCS. Conclusions . 30-CST had the most expressed association with the outcomes of HRQoL in the Estonian population. Subjects with physical performance results under threshold values are at risk of lower HRQoL; therefore, 30-CST is a potential screening indicator for HRQoL assessment.